The gills of Hemichromis fasciatus Peters, 1858 (Teleostei, Ciclidae), a biotope for ectoparasites : structure, heterogeneity and growth models - (:unkn) unknown (My University, 1999)
Fish gills constitute an heterogeneous biotope for many ectoparasite communities. Their modifications during fish maturation are partly at the origin of this heterogeneity. The number of gill filaments and the gill area colonizable by ectoparasites generally increase with the fish age. For Hemichromis fasciatus, an african Cichlidae (Teleostei), this increase of filament number can be fitted by an exponential model, and the colonizable area growth by a polynomial function. These models are compared with those of two temperate teleosts already know.
Keywords: African Research